Chapter Apprendimento post-formale e ricerca collaborativa - FABBRI, LORETTA (Studies on Adult Learning and Education, 2022)
This essay traces Paolo Federighi's research trajectories in Learning and Education for Adults through interviews with the scholar himself conducted over the years. What emerges is a multidisciplinary and international epistemological framework within which are situated the different declinations of counseling as collaborative research, capable of integrating scientific and practical knowledge. The proposed reflection legitimizes the adoption of emergent and multi-methodological approaches, just as it supports the demand for Collaborative Educational Research, capable of holding together communities of diverse stakeholders, such as universities, businesses, and institutional actors.